Biological Characteristics and Whole-Genome Analysis of a Porcine E. coli Phage - Shenghui Wan; Nana Li; Sajid Habib; Pei Zheng; Yanfang Li; Yan Liang; Yonggang Qu (Veterinary Sciences)
(1) Background: In recent years, the increasing emergence of multidrug-resistant pathogens in pig farms has begun to pose a severe threat to animal welfare and, by extension, public health. In this study, we aimed to explore the biological characteristics and genomic features of bacteriophages that are capable of lysing porcine multidrug-resistant E. coli, which was isolated from sewage. In doing so, we provided a reference for phage therapies that can be used to treat multidrug-resistant strains. (2) Method: Using the multidrug-resistant E. coli isolate sq-1 as the host bacterium, bacteriophages were isolated and purified from fecal samples using a double-layer agar plate method. The morphology was observed using a transmission electron microscope, and its host range, optimal multiplicity of infection (MOI), one-step growth curve, thermal stability, acid–base tolerance, and in vitro antibacterial ability were tested. Genomic features were analyzed using whole-genome sequencing. (3) Results: A lytic phage named vB_EcoS_Psq-1 (abbreviated as Psq-1) was successfully isolated. Electron microscopy revealed that Psq-1 belongs to the family of long-tailed phages, possessing clear and transparent plaques of approximately 1 mm in diameter. Psq-1 only lyses the host bacterium and does not affect other E. coli strains or other species of bacteria. The optimal MOI for phage Psq-1 was 0.1, with a latent period of 25 min, an exponential growth period of 25 min, and a lysis yield of 44.21 PFU/cell. Its activity remains stable at temperatures between 40 °C and 60 °C and from pH 4.0 to pH 13.0. Psq-1 exhibited a significant inhibitory effect on E. coli in liquid culture medium. The nucleic acid type of phage Psq-1 was dsDNA, with a total genome length of 44,183 bp and a GC content of 52.16%. No known resistance, lysogenic, or virulence-related genes were detected. The whole genome contains 55 open reading frames (ORFs). (4) Conclusions: This study isolated a bacteriophage that is capable of lysing multidrug-resistant E. coli. Characterized by a narrow E. coli lysis range, a long latent period, limited lytic ability, and stable biological properties, this bacteriophage can serve as a reference isolate for E. coli phages and can provide biological materials and data to support research on bacteriophages that are effective against multidrug-resistant porcine E. coli.